Multifunctional drug delivery nanoparticles for combined chemotherapy/chemodynamic/photothermal therapy against colorectal cancer through synergistic cuproptosis/ferroptosis/apoptosis - Xiuzhang Yan; Heshi Liu; Lei Guo; Chang Liu; Shichen Zhang; Xue Wang; Yixin Tang; Rui Zhou; Xin Jiang; Erlei Wang; Shuohui Gao; Caina Xu (Materials Today Bio)
The use of combination therapies that employ a variety of cell death mechanisms has emerged as a promising avenue of research in the treatment of cancer. However, the optimization of therapeutic synergies when integrating different modes remains a significant challenge. To this end, we developed a multifunctional intelligent drug-carrying nanoparticle (DFMTCH NPs) based on the metal-organic framework MIL-100, loaded with doxorubicin (DOX) and disulfiram (DSF), coated with a Cu-tannic acid (Cu-TA) network and hyaluronic acid (HA), for the purpose of combined chemotherapy/chemodynamic/photothermal anti-cancer therapy. On the one hand, the DFMTCH NPs exhibited a range of therapeutic capabilities, including chemotherapy, photothermal therapy (PTT), and chemodynamic therapy (CDT), which collectively enhanced the anti-tumor efficacy of chemotherapeutic agents. In addition, DFMTCH NPs proved sensitive photoacoustic imaging (PAI) in image-guided therapy. On the other hand, DFMTCH NPs could produce reactive oxygen species (ROS) and consume glutathione (GSH) by amplifying cellular oxidative stress, while causing intracellular mitochondrial dysfunction, inducing effective cuproptosis/ferroptosis/apoptosis to inhibit tumor growth. Collectively, this work provided an innovative strategy for designing multifunctional nanoparticles for effective combination therapies to combat colorectal cancer (CRC).